On the Way to Good Health? Rural Roads and Morbidity in Upland Orissa - Clive Bell; Susanne van Dillen (University of Heidelberg, Department of Economics, 2015)
This paper investigates the effects of India's rural roads program (PMGSY) on morbidity, using data on 279 households drawn from 30 villages in a region of upland Orissa. The households were surveyed in 2010 and 2013, yielding an unbalanced panel of 1580 individuals, 1076 of whom were present in both years. Ten villages had received a direct all-weather road connection by 2013. Treating the village as a unit within the whole road network, the provision of a connection, whether direct or in the neighbourhood, is estimated to have reduced an inhabitant's probability of falling sick by an estimated 3.6 percentage points, and the expected duration of incapacitating illness by 0.46 days, for each km. of unpaved track so replaced.
urn:nbn:de:bsz:16-heidok-195533
Keywords: 330; Rural roads; morbidity; India